Bipolar membrane and method of manufacturing the same
Patent Information
- Application Number
- KR1020207027399
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-03-26
- Filing Date
- 2019-03-19
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2039-03-19
Smart Images

Figure 112020101005069-PCT00005_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a bipolar membrane in which a cation exchange membrane and an anion exchange membrane are joined, and furthermore, to a method for manufacturing the same. Background Technology
[0002] A bipolar membrane is a composite membrane formed by joining a cation exchange membrane and an anion exchange membrane, and by applying voltage to both sides of a bipolar membrane immersed in an aqueous solution, it has the function of causing a phenomenon called hydrolysis, in which water within the membrane dissociates into protons and hydroxide ions. By utilizing this function, an acid or alkali can be produced, for example, from a neutral salt by performing electrodialysis in combination with a bipolar membrane and a cation exchange membrane or an anion exchange membrane.
[0003] In the bipolar membrane described above, a method is employed in which a hydrolysis catalyst that promotes dissociation is provided at the interface between the cation exchange membrane and the anion exchange membrane in order to dissociate water into protons and hydroxide ions at low voltage.
[0004] As such a water-repellent catalyst, for example, Patent Document 1 discloses a metal oxide such as titanium oxide, and a bipolar membrane is proposed in which a layer of this metal oxide is provided at the interface between a cation exchange membrane and an anion exchange membrane.
[0005] In addition, Patent Document 2 discloses that heavy metal ions such as tin and ruthenium are effective as water-removing catalysts, and, for example, a bipolar membrane is proposed in which an anion exchanger or a polymer film capable of introducing an anion exchanger is formed on the surface of a cation exchange membrane ion-exchanged with tin or ruthenium, and an anion exchanger is introduced as needed.
[0006] However, the bipolar membrane proposed in Patent Document 1 requires the metal oxide used as a water-repellent catalyst to be formed as a dense layer at the interface between the cation exchange membrane and the anion exchange membrane, and for this reason, there was a problem that membrane delamination was likely to occur between the cation exchange membrane and the anion exchange membrane during long-term use. In addition, for this reason, after forming a layer of metal oxide on the surface of the cation exchange membrane (or anion exchange membrane), it is necessary to perform an operation to embed metal oxide particles on the surface of the exchange membrane by means of a pressure treatment, etc., which results in low production efficiency.
[0007] In addition, the bipolar membrane of Patent Document 2 has a problem in that the durability of the water-dissolving catalyst is low, and heavy metal ions such as tin or ruthenium are lost outside the membrane during repeated current flow, and as a result, the water-dissolving voltage rises, so improvement regarding this point is necessary. Prior art literature
[0008] Japanese Patent Publication No. 2001-200079, Japanese Patent No. 2524012 The problem to be solved
[0009] Accordingly, the objective of the present invention is to provide a bipolar film capable of stably maintaining a low water discoloration voltage over a long period of time, while effectively solving the problem of film delamination, and a method for manufacturing the same. means of solving the problem
[0010] The inventors examined the conditions for adjusting the hydrolysis catalyst using metal chloride as a starting material regarding the hydrolysis voltage of a bipolar membrane and discovered that by distributing particles of basic metal chloride obtained by adjusting the concentration or pH of the metal chloride at the interface between the cation exchange membrane and the anion exchange membrane, the hydrolysis voltage can be maintained low over a long period of time, and thus completed the present invention.
[0011] According to the present invention, in a bipolar membrane in which a cation exchange membrane and an anion exchange membrane are bonded,
[0012] A bipolar membrane is provided, characterized in that particles of a basic metal chloride are distributed at the interface between the cation exchange membrane and the anion exchange membrane.
[0013] In the bipolar film of the present invention,
[0014] (1) The metal included in the above basic metal chloride is Sn or Ru,
[0015] (2) The particles of the basic metal chloride are distributed in an amount of 0.01 to 5 g / m²
[0016] This is desirable.
[0017] According to the present invention, also
[0018] A process of preparing a pre-fabricated ion exchange membrane as a substrate membrane;
[0019] A particle distribution process for preparing a coating solution in which basic metal chloride particles are dispersed, and applying and drying it on the surface of the substrate film to distribute the basic metal chloride particles on the surface of the substrate film;
[0020] A coating process for forming a counterion exchange resin layer on a substrate film by applying a counterion exchange resin solution to the surface of the substrate film on which the basic metal chloride particles are distributed, and drying it.
[0021] A method for manufacturing a bipolar membrane including is provided.
[0022] In addition, in the present invention, the basic metal chloride is a polyvalent metal chloride into which hydroxide ions have been introduced, and there are chlorides with various degrees of hydroxide ion introduction, for example, having a composition expressed by the following formula (1).
[0023]
[0024] In the formula, M is a polyvalent metal, and
[0025] x and y are non-zero numbers whose sum is the mantissa of the multivalent metal M. Effects of the invention
[0026] The bipolar membrane of the present invention has an important feature in that particles of a basic metal oxide are distributed at the interface between the cation exchange membrane and the anion exchange membrane.
[0027] That is, basic metal chlorides function as hydrolysis catalysts, and since these basic metal chloride particles are distributed as particles at the interface between the cation exchange membrane and the anion exchange membrane, a low hydrolysis voltage can be maintained over a long period of time even when current is continuously applied.
[0028] For example, as shown in the examples described below (see examples for detailed conditions), in the bipolar film of Comparative Example 1, in which basic metal chloride is not distributed, the initial water dissolution voltage is low at 1.2V, but increases significantly to 2.1V after the endurance test. In contrast, in the bipolar film of the present invention in which particles of basic metal chloride (basic tin chloride (II)) are distributed at the bonding interface, the initial water dissolution voltage is 1.1 to 1.4V, and even after the endurance test in which a predetermined current is applied, the water dissolution voltage is 1.7V or lower (specifically 1.1 to 1.4V), and the initial water dissolution voltage is maintained.
[0029] In this way, according to the present invention, the flood voltage can be maintained low over a long period of time.
[0030] Furthermore, although the exact reason why the flood voltage can be maintained low and over a long period by distributing particles of basic metal chloride at the bonding interface as in the present invention has not been precisely elucidated, the inventors estimate as follows.
[0031] In other words, metal-containing hydrolysis catalysts tend to exhibit higher catalytic function as their metal ion generation capacity increases, and basic metal chloride particles possess appropriate solubility in water. Therefore, when a bipolar membrane in which these chloride particles are distributed at the junction interface is immersed in an aqueous solution, the metal ions generated by the dissolution of the chloride in water undergo ion exchange with the ion exchangers of the ion exchange membrane at the junction interface, thereby exhibiting a catalytic function that lowers the hydrolysis voltage. Furthermore, although the metal ions distributed at the junction interface through such ion exchange are gradually lost during current flow, the present invention presumes that new metal ions are supplied from the basic metal chloride particles distributed at the junction interface, and as a result, the low hydrolysis voltage is stably maintained over a long period.
[0032] Furthermore, unlike metal oxides, the basic metal chloride used in the present invention possesses the ability to supply metal ions. For this reason, it has a high catalytic effect, and by making the particle size very small and distributing a small amount at the bonding interface, the ion exchange voltage can be reduced. Consequently, even without performing special operations such as press-fitting as is done when using metal oxides, the decrease in adhesion between ion exchange resins at the bonding interface can be avoided, and film delamination can be effectively avoided, thereby effectively preventing problems such as the generation of bubbles or expansion caused by, for example, partial film delamination. Brief explanation of the drawing
[0033] FIG. 1 is a schematic cross-sectional view of the bipolar film of the present invention. Specific details for implementing the invention
[0034] Referring to FIG. 1, the bipolar membrane (BP) of the present invention is formed by joining a cation exchange membrane (1) and an anion exchange membrane (3), and basic metal chloride particles (5) are distributed as a hydrolysis catalyst at the interface thereof.
[0035] When such a bipolar membrane (BP) is immersed in an aqueous solution and current is passed through it by applying voltage, the water (H2O) that has penetrated into the bipolar membrane (BP) becomes protons (H + ) and hydroxide ions (OH - It is dissociated into ) and protons are released toward the cation exchange membrane (1) and hydroxide ions are released toward the anion exchange membrane (3). Therefore, by using this to conduct electricity in combination with an anion exchange membrane or a cation exchange membrane (i.e., electrodialysis), it is possible to generate and concentrate acid or alkali from organic or inorganic neutral salts and recover them, or to recover acid components from neutral salts, and the basic metal chloride particles promote the dissociation of water as a water dissociation catalyst, thereby enabling the dissociation of water at low voltage.
[0036] In this bipolar membrane (BP), the cation exchange membrane (1) and the anion exchange membrane (3) may be known as themselves.
[0037] <Particles of basic metal chloride (5)>
[0038] Basic metal chlorides are polyvalent metal chlorides into which hydroxide ions have been introduced, and are not particularly limited as long as they can release metal ions as a hydrolysis catalyst. Typically, they have a composition expressed by the following formula (1).
[0039]
[0040] In the formula, M is a polyvalent metal, and
[0041] x and y are non-zero numbers whose sum is the mantissa of the multivalent metal M.
[0042] In the present invention, the basic metal chloride has a hydroxide ion introduction degree T defined by the following formula (2) of 20 to 95%, preferably 30 to 90%, and more preferably 40 to 85%.
[0043]
[0044] If the value of T is less than 20%, there is a concern that the catalytic function may not be able to be exerted for a long period of time, while if it is greater than 90%, the ability to supply metal ions decreases, and there is a tendency for sufficiently high catalytic activity not to be obtained.
[0045] Examples of heavy metals such as Al, Ti, Cr, Fe, Zn, Zr, Ru, Pd, Sn, and Pb can be used as polyvalent metal M included in the basic metal chloride. In terms of catalytic activity, Cr, Ru, and / or Sn are preferred, Ru and / or Sn are more preferred, and Sn is particularly preferred.
[0046] The amount of particles (5) of basic metal chloride distributed at the interface between the cation exchange membrane (1) and the anion exchange membrane (3) is preferably 0.01 to 5 g / m², more preferably 0.05 to 2 g / m², and particularly preferably 0.1 to 1 g / m².
[0047] If the distribution amount of basic metal chloride particles (5) exceeds the above range, there is a risk of problems such as an increase in the electrical resistance of the bipolar membrane and a decrease in the adhesion between the cation exchange membrane and the anion exchange membrane. On the other hand, if the distribution amount of basic metal chloride particles (5) is less than the above range, there is a risk that metal ions as a water dissolution catalyst cannot be continuously replenished over a long period, and as a result, the period during which a low water dissolution voltage can be maintained tends to be shortened.
[0048] In addition, the number average particle size (Dn) of the basic metal chloride particles (5), obtained by analyzing particle images observed by a scanning electron microscope (SEM), is preferably 0.05 to 10 μm, and furthermore, 0.1 to 5 μm. The measurement of the number average particle size (Dn) by a scanning electron microscope (SEM) involves measuring the particle sizes of 100 or more particles based on SEM images observed at a magnification of about 3,000 to 10,000 times, and determining the number average particle size based on these values. This is because when the number average particle size of the basic metal chloride particles (5) is greater than 10 μm, there is a tendency for the water dissolution voltage to rise. This is thought to be because the specific surface area of the basic metal chloride particles (5) is small, so the rate of metal ion release is slow, and the metal ions that leak out of the bipolar membrane cannot be completely replenished, and the adhesion of the interface is poor, making it easy for blisters to form.
[0049] <Manufacturing of Bipolar Membranes (BP)>
[0050] The bipolar membrane (BP) of the present invention is manufactured by, for example, preparing a pre-fabricated ion exchange membrane as a substrate, preparing a coating solution in which basic metal chloride particles are dispersed, distributing the basic metal chloride particles (5) on the surface of the substrate membrane by applying and drying the coating solution on the substrate membrane, and then applying a counter-ion exchange resin solution to the substrate membrane and drying it to form a counter-ion exchange resin layer on the substrate membrane.
[0051] Hereinafter, a method for manufacturing a bipolar membrane of the present invention in which a cation exchange membrane (1) is used as a substrate membrane will be described.
[0052] 1. Formation of a cation exchange membrane (1)
[0053] As a cation exchange resin forming a cation exchange membrane (1), a known resin can be used. For example, a resin in which a cation exchange group, such as a sulfonic acid group, a carboxylic acid group, or a phosphonic acid group is introduced into an aromatic ring present in a main chain or side chain of polysulfone, polystyrene, etc. is suitably used.
[0054] In addition, it is preferable that the cation exchange membrane (1) contains a reinforcing material to ensure membrane strength. The reinforcing material may take any form, such as a woven fabric, a non-woven fabric, or a porous film, but a woven fabric is preferred in terms of strength. Furthermore, any material may be used as the reinforcing material as long as a certain strength is obtained. Specifically, polyolefins such as polyethylene or polypropylene; polyvinyl chloride, etc. are suitably used.
[0055] The cation exchange membrane (1) can be formed according to a conventionally known method. Representative methods include the following.
[0056] That is, a monomer composition containing a monomer having a cation exchange group, a crosslinkable monomer (e.g., divinylbenzene, etc.), and a polymerization initiator is impregnated into a reinforcing material such as a woven fabric by spraying, coating, etc., and then the monomer composition is polymerized to produce a cation exchange resin, thereby obtaining a cation exchange membrane (1) of the desired type.
[0057] In addition, instead of the monomer having the above-mentioned cation exchange group, a monomer having a reactive group capable of introducing a cation exchange group (e.g., styrene) may be used to produce a cation exchange resin precursor by polymerizing in the same manner as above, and then a desired ion exchange group may be introduced into this precursor by treatment such as sulfonation or hydrolysis to obtain a desired cation exchange membrane (1).
[0058] The thickness of the cation exchange membrane (1) manufactured as described above is preferably in the range of 10 to 500 μm, more preferably 100 to 300 μm. If this thickness is too thin, there is a risk that the strength of the cation exchange membrane (1) will be significantly reduced. If the thickness is excessively thick, the membrane resistance will increase, and as a result, there is a risk that problems such as an increase in bipolar voltage will occur.
[0059] In addition, the ion exchange capacity of the cation exchange membrane is generally preferably in the range of 0.1 to 4 meq / g, particularly 0.5 to 2.5 meq / g, from the perspective of membrane characteristics as a bipolar membrane, such as voltage drop or current efficiency. Furthermore, the membrane resistance is also preferably in the range of 15 Ω·cm² or less, particularly 1 to 5 Ω·cm².
[0060] In the present invention, prior to the distribution of basic metal chloride particles (5) onto the surface of the cation ± ring membrane (1), it is preferable to roughen the surface of the cation exchange membrane (1) (the side on which the basic metal chloride particles (5) are distributed) by polishing with sandpaper or sandblasting. This is because the anchoring effect is increased, and a bipolar membrane with higher adhesion between the cation exchange membrane (1) and the anion exchange membrane (3) can be obtained.
[0061] 2. Distribution of basic metal chloride particles (5)
[0062] Next, particles (5) of a basic metal chloride are distributed on the surface of the cation exchange membrane (1) formed as described above. There are no particular limitations on the method of distributing the basic metal chloride particles (5), but representative methods include applying a coating solution in which the basic metal chloride particles are dispersed in water to the surface of the cation exchange membrane (1) by spraying, immersion, screen printing, etc. Among these, application by immersion is preferred in terms of manufacturing cost and simplification of the manufacturing process.
[0063] A coating solution in which such basic metal chloride particles are dispersed can be prepared by adding the metal chloride to water, utilizing the fact that the metal chloride is water-soluble, and can be obtained by adjusting the amount of metal chloride added to water or the pH according to the type of metal so that the basic metal chloride is present.
[0064] For example, a coating solution in which particles of basic tin chloride (hereinafter referred to as basic tin chloride), a representative basic metal chloride, are dispersed can be prepared by the following method.
[0065] The first method is a method of precipitating particles of basic tin chloride (II) by adjusting the amount of tin chloride (II) added to water.
[0066] That is, in the aqueous solution obtained by adding tin chloride (II) to water so that the amount of tin chloride (II) is at a high concentration of 1 mass% or more, tin chloride (II) is usually water-soluble, so tin chloride (II) is dissolved under strong acidic conditions where the pH of the aqueous solution is less than 1.0.
[0067] However, if the amount is less than 1 mass%, the acidity of the aqueous solution is weakened according to the amount, with the pH being 1.0 or higher, particularly in the range of 1.0 to 12.0, and further in the range of 1.5 to 5.0. And under this weakened acidity state, the dissolved tin chloride (II) is hydrolyzed as shown in the following formula to produce basic tin chloride (II).
[0068] SnCl2 + 2H2O → Sn(OH)Cl↓ + HCl
[0069] In this case, most of the basic tin chloride (II) precipitates when the liquid temperature is 40°C or lower, preferably 5°C to 35°C. Therefore, by adding tin chloride (II) to water such that the amount of tin chloride (II) is less than 1 mass%, a coating solution in which particles of basic tin chloride (II) are dispersed is obtained.
[0070] For example, if the concentration (input amount) of tin chloride (II) is 1 mass% or more, substitution with hydroxide ions by the above reaction does not substantially occur. As a result, basic tin chloride particles are not precipitated, and long-term stability of the hydroxide catalyst function is not obtained.
[0071] In the present invention, when preparing a coating solution by adjusting the amount of tin chloride (II) added to water to less than 1 mass% as described above, the amount of tin chloride (II) added is preferably 0.05 to 0.6 mass%, and particularly preferably 0.1 to 0.4 mass%. If the amount of tin chloride (II) added is excessively low, the distribution amount of basic metal chloride decreases, making it difficult to maintain the water damage catalyst function for a long period.
[0072] The second method is a method of adjusting the pH of an aqueous solution obtained by adding tin chloride (II) to water.
[0073] That is, as can be understood from the above description, the pH of the liquid obtained by dissolving tin chloride (II) at a high concentration of 1.0 mass% or more at a liquid temperature of 40°C or lower (especially 5 to 35°C) becomes less than 1.0. However, if a basic aqueous solution such as sodium hydroxide solution or ammonia water is added to this high concentration liquid to adjust the pH to a range of 1.0 to 12.0, preferably 1.5 to 5.0, basic tin chloride (II) is produced, and subsequently, a coating liquid in which particles of basic tin chloride (II) are dispersed can be obtained.
[0074] For example, in a solution with a pH of less than 1.0, basic tin(II) chloride is not precipitated, and when the pH becomes 12.0 or higher, the precipitation of Sn(OH)2 becomes dominant, and the catalytic activity is reduced.
[0075] When precipitating basic tin chloride (II) by adjusting the pH in this way, it is preferable to set the amount of tin chloride (II) added to water to typically 1.0 to 10.0 mass%, preferably 1.0 to 5.0 mass%, and more preferably 1.2 to 2.0 mass%. If the amount added to water is increased beyond what is necessary, the particle size of the precipitated basic tin chloride (II) becomes too large, which is undesirable.
[0076] In addition, even when preparing a coating solution by setting the amount of tin chloride (II) added to less than 1.0 mass%, it is also possible to adjust the pH of the solution to a range of 1.0 to 12.0 to promote the precipitation of basic tin chloride.
[0077] The method of preparing a coating solution as described above can also be applied to the preparation of a coating solution in which basic metal chloride particles containing metals other than tin are dispersed. In particular, pH adjustment is required for the preparation of a coating solution in which basic ruthenium chloride particles are dispersed, and a salt coating solution in which basic ruthenium chloride is dispersed can be obtained by adjusting the pH to 1.0 or higher (preferably 1.0 to 12.0, more preferably 1.5 to 5.0) at a liquid temperature of typically 40°C or lower (especially 5 to 35°C).
[0078] As described above, by applying a coating solution (aqueous solution) in which basic metal chloride particles are dispersed to the cation exchange membrane (1), not only can basic metal chloride particles (5) be distributed on the surface of the cation exchange membrane (1), but ion exchange can also be performed between the metal ions in the aqueous solution and the ion exchangers of the cation exchange resin constituting the surface (junction surface) of the cation exchange membrane (1). Therefore, by this method, a bipolar membrane (BP) in which metal ions having catalytic activity are introduced from the beginning of production can be manufactured, and such a bipolar membrane (BP) can exhibit high catalytic activity immediately after the start of electrodialysis.
[0079] In addition, as another method of distributing basic metal chloride particles (5) on the cation exchange membrane (1), a method of applying powder of basic metal chloride by spraying, transferring, etc. may be adopted.
[0080] In this method, prior to the application of powder of a basic metal chloride, a solution containing metal ions is applied by immersion, spraying, etc., thereby allowing ion exchange between the metal ions and the counter ions of the ion exchanger near the surface of the cation exchange membrane (1). As a result, metal ions having catalytic activity can be introduced to the surface of the cation exchange membrane (1), just as in the case where an aqueous solution of metal chloride in which the basic metal chloride particles are dispersed is applied, and a bipolar membrane (BP) exhibiting high catalytic activity is obtained immediately after the start of electrodialysis.
[0081] In addition, powder of a basic metal chloride may be applied directly to the cation exchange membrane (1) without performing the above-mentioned ion exchange. In this case, at the stage of fabricating the bipolar membrane (BP), metal ions having catalytic activity do not exist near the interface between the cation exchange membrane (1) and the anion exchange membrane (3). However, during electrodialysis, the bipolar membrane (BP) is placed in water, and the basic metal chloride releases metal ions, and these metal ions exhibit catalytic activity. Therefore, the bipolar membrane (BP) fabricated by this method requires some time after the start of electrodialysis until high catalytic activity is obtained, but after a certain amount of metal ions are released from the basic metal chloride, it can exhibit catalytic activity equivalent to that of the bipolar membrane (BP) fabricated by the above-mentioned method.
[0082] 3. Formation of anion exchange membrane
[0083] Next, an anion exchange membrane (3) is formed on the surface of the cation exchange membrane (1) on which particles (5) of the basic metal chloride are distributed as described above. As the anion exchange resin for forming the anion exchange membrane (3), a known material can be used. For example, an anion exchange group such as a 1st to 3rd amino group or a quaternary ammonium base is introduced into the aromatic ring present in the main chain or side chain of polysulfone, polystyrene, etc. is used.
[0084] There are no particular restrictions on the method of forming the anion exchange membrane (3). A representative method is, for example, the coating method.
[0085] Specifically, a coating solution containing an anion exchange resin precursor having a reactor capable of introducing anion exchangers is applied to the surface of a cation exchange membrane (1), and if necessary, the solvent in the coating solution is removed by drying, and then a desired anion exchanger is introduced into the anion exchange resin precursor by treatment such as amination or alkylation, thereby obtaining a bipolar membrane (BP) in which an anion exchange membrane (3) is formed on the cation exchange membrane (1).
[0086] In addition, an anion exchange resin film (3) can be formed in one step by applying a coating solution containing an anion exchange resin to the surface of a cation exchange membrane (1) and then drying it.
[0087] In addition, an anion exchange membrane can be formed in one step by applying a polar organic solvent solution of an anion exchange resin precursor resin having a reactive group capable of introducing an anion exchanger and an anion exchanger introductory agent to the surface of the cation exchange membrane, and then removing the polar organic solvent.
[0088] The thickness of the anion exchange membrane (3) manufactured as described above is preferably in the range of 1 to 200 μm. If this thickness is too thin, there is a risk that the strength of the anion exchange membrane (3) will be significantly reduced. If the thickness is excessively thick, there is a risk that problems such as an increase in bipolar voltage may occur.
[0089] The ion exchange capacity of such anion exchange membranes, like that of the substrate cation exchange membranes, is generally in the range of 0.1 to 4 meq / g, and particularly 0.5 to 2.5 meq / g, in terms of membrane characteristics as bipolar membranes.
[0090] 4. Post-processing
[0091] Additionally, after the formation of the anion exchange membrane (3), appropriate heat treatment may be performed. By doing so, the anion exchange membrane (3) penetrates into the rough surface of the cation exchange membrane (1), and as a result, the bonding strength between the cation exchange membrane (1) and the anion exchange membrane (3) is significantly improved. It is preferable to perform this heat treatment at a temperature higher than, for example, the softening point of the reinforcing material in the cation exchange membrane, and it is also preferable to perform it under pressure to increase the anchoring effect by the rough surface. For example, pressure can be applied by placing it on a steel plate heated to the above temperature range or by passing it between rollers.
[0092] The bipolar membrane (BP) of the present invention manufactured as described above can maintain a low water dissolution voltage over a long period of time because particles of basic metal chloride are distributed at the interface between the cation exchange membrane (1) and the anion exchange membrane (3).
[0093] Specifically, as measured in the embodiments described below, a current density of 10 A / dm 2 Under these conditions, it is possible to suppress the water damage voltage after performing electrodialysis for 6 months to 25% or less of the initial water damage voltage.
[0094] The bipolar membrane of the present invention allows for the wide application of manufacturing conditions, such as temperature, particularly during the production of acids and alkalis. Additionally, it is cut to an appropriate size and provided for use or sale.
[0095] Examples
[0096] Hereinafter, to specifically explain the present invention, examples and comparative examples will be described, but the present invention is not limited thereto in any way. Furthermore, in the examples and comparative examples, the characteristics of the bipolar film were determined by the following measurements.
[0097] [Measurement of Ion Exchange Capacity of Ion Exchange Membranes]
[0098] The ion exchange membrane was immersed in a 1 mol / L-HCl aqueous solution for more than 10 hours.
[0099] Afterwards, in the case of the cation exchange membrane, the counter ion of the ion exchanger was replaced from hydrogen ions to sodium ions with a 1 mol / L-NaCl aqueous solution, and the liberated hydrogen ions were quantified using a potentiometric titration apparatus (COMTITE-900, manufactured by Hiranuma Sangyo Co., Ltd.) with an aqueous sodium hydroxide solution (Amol).
[0100] Meanwhile, in the case of an anion exchange membrane, the counter ion was replaced from chloride ion to nitrate ion with a 1 mol / L NaNO3 aqueous solution, and the liberated chloride ion was quantified using a potentiometric titration apparatus (COMTITE-900, manufactured by Hiranuma Sangyo Co., Ltd.) with an aqueous silver nitrate solution (A mol).
[0101] Next, the same ion exchange membrane was immersed in a 1 mol / L NaCl aqueous solution for at least 4 hours, and then dried under reduced pressure at 60°C for 5 hours to measure the weight at dry (Dg). Based on the above measurements, the ion exchange capacity of the ion exchange membrane was calculated using the following formula.
[0102] Ion exchange capacity = A × 1000 / D [meq / g - dry mass]
[0103] [Method for exfoliating a bipolar membrane into a cation membrane and an anion membrane]
[0104] Using a 2-chamber cell having the following configuration, at a liquid temperature of 25℃ and a current density of 30A / dm² 2 The cation and anion membranes of the bipolar membrane were delaminated by applying current for 5 hours under the conditions. That is, the current applied in this cell configuration has the positive and negative poles reversed compared to current that dissociates water within the membrane into protons and hydroxide ions. Due to this reverse current application, water dissociation does not occur, and protons in the hydrochloric acid solution and hydroxide ions in the sodium hydroxide solution move toward the interface of the bipolar membrane. Consequently, water is forcibly generated at the anion / cation membrane interface of the bipolar membrane, and a delamination action occurs between the anion membrane and the cation membrane.
[0105] Cathode (Pt plate) (1.0 mol / L-NaOH) / Measurement bipolar membrane / (1.0 mol / L-HCl) Anode (Pt plate)
[0106] [Identification of Basic Metal Chloride Particles]
[0107] The bipolar membrane of the measurement target was exfoliated into a cation membrane and an anion membrane by the method described above. After drying either the obtained cation membrane or the anion membrane, some of the particles present on the exfoliated surface were recovered using a brush. By analyzing this powder using an X-ray diffraction device (Rigaku, SmartLab), it was confirmed that the individually present particles were basic metal chlorides.
[0108] [Measurement of the amount of basic metal chloride particles]
[0109] The bipolar membrane of the measurement target was separated into a cation membrane and an anion membrane by the method described above. Using the obtained cation membrane and anion membrane, the amount of basic metal chloride particles present at the interface between the cation exchange membrane and the anion exchange membrane was determined by the following method.
[0110] After cutting the cation exchange membrane and the anion exchange membrane into pieces of 10 cm² each, 100 ml of a 0.5 mol / L-HCl aqueous solution was flowed over the surface of each stripped side to wash away all basic metal chloride particles present on the stripped side surface, and the entire amount of the solution was recovered. The volume of the recovered aqueous solution was adjusted to a constant amount, and the amount of metal element Ag was quantified using an inductively coupled plasma emission spectrometer (Thermo Scientific, "iCAP 6500 DUO"). The amount of basic metal chloride D (g / m²) present at the interface between the cation exchange membrane and the anion exchange membrane was calculated using the following formula.
[0111] Dg / ㎡=(A×B) / (0.001×C)
[0112] A: Amount of metal element (g)
[0113] B: Molecular weight of basic metal chloride calculated from the hydroxide ion introduction degree T
[0114] C: Atomic weight of a metallic element
[0115] [Measurement of Number Average Particle Size (Dn) of Basic Metal Chlorides]
[0116] For the bipolar membrane of the measurement target, the membrane was exfoliated into a cation membrane and an anion membrane by the method described above. For either of the obtained cation membrane or anion membrane, the basic metal chloride present on the exfoliated surface was observed using a scanning electron microscope (SEM) (SU3500, manufactured by Hitachi High Technologies) at a magnification of about 3,000 to 10,000 times, and the particle size of more than 100 particles was measured, and the number average particle size (Dn) was calculated based on these values.
[0117] [Measurement of Hydroxide Ion Introduction T in Basic Metal Chlorides]
[0118] For the bipolar membrane to be measured, it was exfoliated into a cation membrane and an anion membrane by the method described above. For either of the obtained cation membrane or anion membrane, the exfoliated surface was analyzed by X-ray photoelectron spectroscopy (XPS), and the relative molar ratio (y) of inorganic Cl element to metal was determined for the catalyst particles present on the exfoliated surface. The degree of hydroxide ion introduction T (%) was calculated by the following formula.
[0119] T(%) = (metal valence - y) / (metal valence) × 100
[0120] [Measurement of Bipolar Film Flushing Voltage]
[0121] Four cells having the following configuration were used.
[0122] In addition, when forming the 4-cell, the bipolar membrane (BP membrane) of Astomu Inc. (Neoceptor BP-1E) was used as a standard bipolar membrane along with the bipolar membrane of the measurement target.
[0123] Anode (Pt plate) (1.0 mol / L-NaOH) / Standard BP film / (1.0 mol / L-NaOH) / BP film of measurement / (1.0 mol / L-HCl) / Standard BP film / (1.0 mol / L-HCl) / Cathode (Pt plate)
[0124] Liquid temperature 25℃, current density 10A / dm² 2 The bipolar voltage was measured under the conditions. The bipolar voltage was measured using a platinum wire electrode installed with a bipolar membrane.
[0125] [Measurement of Bipolar Membrane Flood Damage Efficiency]
[0126] Using a 2-chamber cell having the following configuration, at a liquid temperature of 25℃ and a current density of 10A / dm² 2 After energizing for 20 hours under the conditions, the amounts of acid and base in both chambers were quantified. From the amounts of acid and base obtained, the current efficiency of acid and base generation was calculated, and the average value of the two was obtained as the bipolar membrane hydrolysis efficiency.
[0127] Anode (Pt plate) (1.0 mol / L-NaOH) 100 ml / BP membrane of measurement / (1.0 mol / L-HCl) 100 ml / Cathode (Pt plate)
[0128] [Adhesion of Bipolar Membranes]
[0129] After immersing the bipolar membrane in a 6.0 mol / L aqueous sodium hydroxide solution at 25°C for 1 hour, the membrane was removed and immersed in pure water at 25°C for 1 hour. After removing the membrane from the pure water, it was analyzed using an image processing system (IP-1000PC manufactured by Asahi Engineering Co., Ltd.) to calculate the ratio of abnormal areas (parts where blisters are occurring) per 1 cm² of the membrane as the peeling area (%).
[0130] [Long-term operation of bipolar membranes]
[0131] Using the 4-cell used in the above [Measurement of Bipolar Film Disruption Voltage], the bipolar film disruption voltage was measured after operating for 6 months under the same conditions.
[0132] [Preparation of Solution for Anion Exchange Membrane Formation]
[0133] 100g of a copolymer containing a polystyrene segment (65 mass%) and a hydrogenated polyisoprene segment (35 mass%) was dissolved in 1000g of chloroform, 100g of chloromethylmethyl ether and 10g of tin chloride were added, and the mixture was reacted at 40°C for 15 hours.
[0134] Next, a chloromethylated styrene-based block copolymer was obtained by precipitating and washing in methanol, and then drying. Next, chloromethylated polystyrene with a molecular weight of 5000 was mixed with the above-mentioned chloromethylated styrene-based copolymer to prepare a mixture in which the proportion of chloromethylated polystyrene was 40 mass%.
[0135] The chloromethylated polymer mixture obtained in this way was dissolved in tetrahydrofuran to make a 25 mass% solution, and then 8 mass% of N,N,N',N'-tetramethyl-1,6-hexanediamine was added to this solution to prepare a solution for forming an anion exchange membrane containing an anion exchange resin precursor resin and an anion exchanger introduction agent.
[0136] <Example 1>
[0137] As a cation exchange membrane, Astomuz Co., Ltd. Neoceptor CMX (containing polyvinyl chloride woven fabric as a reinforcing material, cation exchange capacity 1.6 meq / g, membrane resistance 2.8 Ω·cm²) was prepared.
[0138] Tin chloride (II) was dissolved in water at a concentration of 0.4 mass% at 25°C and stirred, and left for 30 minutes, resulting in the precipitation of particles and a suspension.
[0139] This suspension was used as a catalyst particle coating solution.
[0140] Next, the cation exchange membrane, on which irregularities had been formed on its surface using sandpaper (CC 200 Cw), was immersed in the catalyst particle coating solution at 25°C for 1 hour, and then air-dried at room temperature to distribute catalyst particles on its surface. A solution for forming an anion exchange membrane was applied to one side of the cation exchange membrane, and the membrane was left at room temperature to form an anion exchange membrane layer, thereby manufacturing a bipolar membrane.
[0141] In addition, the anion exchange capacity of the anion exchange membrane obtained by applying the above-mentioned solution for forming an anion exchange membrane onto a polyester film and leaving it at room temperature to dry was measured to be 1.8 meq / g. From this, it was confirmed that the anion exchange capacity of the anion exchange membrane layer in the above-mentioned bipolar membrane is equivalent.
[0142] Regarding the above bipolar membrane, it was confirmed by the above method that the particles present at the interface between the cation exchange membrane and the anion exchange membrane are basic tin chloride (II) particles. In addition, the amount of this basic tin chloride (II) was measured to be 0.5 g / m².
[0143] In addition, the basic tin chloride (II) particles had a number average particle size (Dn) of 2 μm and a hydroxide ion introduction degree T of 60%.
[0144] In addition, the characteristics of this bipolar membrane were measured, and the water leakage voltage was 1.1V and the water leakage efficiency was 99.5%.
[0145] In addition, the water voltage of this membrane was measured over a long period and was 1.1V at the time of initial energization, and was 1.1V after 6 months of energization, and the adhesion of the bipolar membrane was measured and no bubbles were produced.
[0146] <Example 2>
[0147] A bipolar film was prepared by performing the same operation as in Example 1, except that the preparation of the catalyst particle coating solution in Example 1 was carried out by dissolving tin chloride (II) in water at a concentration of 0.9 mass% at 25°C.
[0148] Regarding the obtained bipolar membrane, it was confirmed by the above method that the particles present at the interface between the cation exchange membrane and the anion exchange membrane are basic tin chloride (II) particles.
[0149] The amount of this basic tin chloride (II) particle was measured to be 1.0 g / m².
[0150] In addition, the basic tin chloride (II) particles had a number average particle size (Dn) of 3 μm and a hydroxide ion introduction degree T of 25%.
[0151] The results of measuring the characteristics of this bipolar membrane are shown in Table 1.
[0152] <Example 3>
[0153] A bipolar film was prepared by performing the same operation as in Example 1, except that the preparation of the catalyst particle coating solution in Example 1 was carried out by dissolving tin chloride (II) in water at a concentration of 0.05 mass% at 25°C.
[0154] Regarding the obtained bipolar membrane, it was confirmed by the above method that the particles present at the interface between the cation exchange membrane and the anion exchange membrane are basic tin chloride (II) particles.
[0155] In addition, the amount of this basic tin chloride (II) particle was measured to be 0.09 g / m².
[0156] In addition, the basic tin chloride (II) particles had a number average particle size (Dn) of 1 μm and a hydroxide ion introduction degree T of 80%.
[0157] The results of measuring the characteristics of this bipolar membrane are shown in Table 1.
[0158] <Example 4>
[0159] In Example 1, a bipolar membrane was prepared by performing the same operation as in Example 1, except that the preparation of the catalyst particle coating solution was carried out by dissolving tin (II) in water at a concentration of 0.4 mass% at 25°C, adding sodium hydroxide to the solution under stirring to adjust the pH to 2.0, and leaving it for 30 minutes.
[0160] Regarding the obtained bipolar membrane, it was confirmed by the above method that the particles present at the interface between the cation exchange membrane and the anion exchange membrane are basic tin chloride (II) particles.
[0161] In addition, the amount of this basic tin chloride (II) particle was measured to be 0.6 g / m².
[0162] In addition, the basic tin chloride (II) particles had a number average particle size (Dn) of 2 μm and a hydroxide ion introduction degree T of 65%.
[0163] The results of measuring the characteristics of this bipolar membrane are shown in Table 1.
[0164] <Example 5>
[0165] In Example 4, a bipolar membrane was prepared by performing the same operation as in Example 4, except that the preparation of the catalyst particle coating solution was carried out by dissolving ruthenium(III) chloride in water at a concentration of 1.0 mass% at 25°C, adding sodium hydroxide to the solution under stirring to adjust the pH to 2.0, and leaving it for 30 minutes.
[0166] Regarding the obtained bipolar membrane, it was confirmed by the above method that the particles present at the interface between the cation exchange membrane and the anion exchange membrane are basic ruthenium chloride (III) particles.
[0167] In addition, the amount of this basic ruthenium chloride (III) particle was measured to be 0.4 g / m².
[0168] In addition, the basic ruthenium chloride (III) particles had a number average particle size (Dn) of 2 μm and a hydroxide ion introduction degree T of 42%.
[0169] The results of measuring the characteristics of this bipolar membrane are shown in Table 1.
[0170] <Example 6>
[0171] In Example 4, a bipolar membrane was prepared by performing the same operation as in Example 4, except that the preparation of the catalyst particle coating solution was carried out by dissolving ruthenium(III) chloride in water at a concentration of 3.0 mass% at 25°C, adding sodium hydroxide to the solution under stirring to adjust the pH to 2.5, and leaving it for 30 minutes.
[0172] Regarding the obtained bipolar membrane, it was confirmed by the above method that the particles present at the interface between the cation exchange membrane and the anion exchange membrane are basic ruthenium chloride (III) particles.
[0173] In addition, the amount of this basic ruthenium chloride (III) particle was measured to be 1.1 g / m².
[0174] In addition, the basic ruthenium chloride (III) particles had a number average particle size (Dn) of 4 μm and a hydroxide ion introduction degree T of 50%.
[0175] The results of measuring the characteristics of this bipolar membrane are shown in Table 1.
[0176] <Example 7>
[0177] A bipolar membrane was prepared by performing the same operation as in Example 1, except that as the solution for forming the anion exchange membrane in Example 1, a solution of aminated polysulfone (polysulfone chloromethylated and then quaternary ammonium vaporized with trimethylamine) dissolved in a mixed solvent of methanol / chloroform (1:1 vol) at 15 mass% was used.
[0178] In addition, for the obtained bipolar membrane, the anion exchange capacity of the anion exchange membrane was 1.7 meq / g.
[0179] Regarding the obtained bipolar membrane, it was confirmed by the above method that the particles present at the interface between the cation exchange membrane and the anion exchange membrane are basic tin chloride (II) particles.
[0180] In addition, the amount of these basic tin chloride (II) particles was measured to be 0.6 g / m². Also, the basic tin chloride (II) particles had a number average particle size (Dn) of 2 μm and a hydroxide ion introduction degree T of 60%.
[0181] The results of measuring the characteristics of this bipolar membrane are shown in Table 1.
[0182] <Example 8>
[0183] A monomer composition comprising 70 parts by mass of styrene, 20 parts by mass of chloromethylstyrene, 10 parts by mass of divinylbenzene (57% product), 5 parts by mass of benzoyl peroxide, 10 parts by mass of tributyl acetyl citrate, and 50 parts by mass of polyvinyl chloride powder was prepared, and a polyethylene woven fabric (50 denier, mesh length:width 156:100 / inch, monofilament, wire diameter 86 μm) was immersed in it at 25°C under atmospheric pressure for 10 minutes to attach the monomer composition.
[0184] Next, the woven fabric was removed from the monomer composition, and both sides of the membrane were coated using a 100 μm thick film of polyethylene terephthalate as a release agent, followed by heat polymerization at 80°C for 5 hours under pressure. The obtained membrane was immersed in a mixture of 98% concentrated sulfuric acid and chlorosulfonic acid with a purity of 90% or higher at 40°C for 60 minutes to obtain a sulfonic acid-type cation exchange membrane (cation exchange capacity 2.1 meq / g, membrane resistance 2.6 Ω·cm²).
[0185] A bipolar membrane was prepared by performing the same operation as in Example 1, except that the sulfonic acid-type cation exchange membrane prepared above was used as the cation exchange membrane in Example 1.
[0186] Regarding the obtained bipolar membrane, it was confirmed by the above method that the particles present at the interface between the cation exchange membrane and the anion exchange membrane are basic tin chloride (II) particles.
[0187] In addition, the amount of this basic tin chloride (II) particle was measured to be 0.5 g / m².
[0188] In addition, the basic tin chloride (II) particles had a number average particle size (Dn) of 2 μm and a hydroxide ion introduction degree T of 60%.
[0189] The results of measuring the characteristics of this bipolar membrane are shown in Table 1.
[0190] <Example 9>
[0191] A monomer composition comprising 70 parts by mass of styrene, 20 parts by mass of chloromethylstyrene, 10 parts by mass of divinylbenzene (57% product), 5 parts by mass of benzoyl peroxide, 10 parts by mass of tributyl acetyl citrate, and 50 parts by mass of polyvinyl chloride powder was prepared, and a polyethylene nonwoven fabric (porosity 78%, weight per unit area 10 g / m², fiber diameter 12 μm) was immersed in it at 25°C for 10 minutes under atmospheric pressure to attach the monomer composition.
[0192] Next, the nonwoven fabric was removed from the monomer composition, and both sides of the film were coated with a 100 μm thick film of polyethylene terephthalate as a release agent, and then heated and polymerized at 80°C for 5 hours under pressure.
[0193] The obtained membrane was immersed in a mixture of 98% concentrated sulfuric acid and chlorosulfonic acid with a purity of 90% or higher at 40°C for 60 minutes to obtain a sulfonic acid-type cation exchange membrane (cation exchange capacity 2.5 meq / g, membrane resistance 1.8 Ω·cm²).
[0194] A bipolar membrane was prepared by performing the same operation as in Example 1, except that the sulfonic acid-type cation exchange membrane prepared as above was used as the cation exchange membrane in Example 1.
[0195] Regarding the obtained bipolar membrane, it was confirmed by the above method that the particles present at the interface between the cation exchange membrane and the anion exchange membrane are basic tin chloride (II) particles.
[0196] In addition, the amount of this basic tin chloride (II) particle was measured to be 0.5 g / m².
[0197] In addition, the basic tin chloride (II) particles had a number average particle size (Dn) of 2 μm and a hydroxide ion introduction degree T of 60%.
[0198] The results of measuring the characteristics of this bipolar membrane are shown in Table 1.
[0199] <Example 10>
[0200] Tin chloride (II) was dissolved in water at a concentration of 0.6 mass% at 25°C and stirred, and left for 30 minutes to obtain a suspension in which precipitation of particles occurred. This suspension was filtered, and the filtrate was dried to obtain catalyst particle powder.
[0201] A bipolar membrane was prepared by performing the same operation as in Example 1, except that the distribution of catalyst particles to the surface of the cation exchange membrane in Example 1 was achieved by applying the catalyst particle powder with a finger to a surface on which irregularities had been formed beforehand using sandpaper on the cation exchange membrane.
[0202] Regarding the obtained bipolar membrane, it was confirmed by the above method that the particles present at the interface between the cation exchange membrane and the anion exchange membrane are basic tin chloride (II) particles.
[0203] In addition, the amount of this basic tin chloride (II) particle was measured to be 2.0 g / m².
[0204] In addition, the basic tin chloride (II) particles had a number average particle size (Dn) of 3 μm and a hydroxide ion introduction degree T of 38%.
[0205] The results of measuring the characteristics of this bipolar membrane are shown in Table 1.
[0206] <Example 11>
[0207] Ruthenium chloride (III) was dissolved in water at a concentration of 0.9 mass% at 25°C, sodium hydroxide was added to the solution under stirring to adjust the pH to 2.0, and the solution was left for 30 minutes to precipitate particles, thereby obtaining a suspension. This suspension was filtered, and the filtrate was dried to obtain catalyst particle powder.
[0208] In Example 10, a bipolar membrane was prepared by performing the same operation except that the catalyst particle powder was used as the catalyst particle powder applied to the surface of the cation exchange membrane with a finger.
[0209] Regarding the obtained bipolar membrane, it was confirmed by the above method that the particles present at the interface between the cation exchange membrane and the anion exchange membrane are basic ruthenium chloride (III) particles.
[0210] In addition, the amount of this basic ruthenium chloride (III) particle was measured to be 2.2 g / m².
[0211] In addition, the basic ruthenium chloride (III) particles had a number average particle size (Dn) of 3 μm and a hydroxide ion introduction degree T of 45%.
[0212] The results of measuring the characteristics of this bipolar membrane are shown in Table 1.
[0213] <Example 12>
[0214] As an anion exchange membrane, Astomuz Co., Ltd. Neoceptor AMX (containing polyvinyl chloride woven fabric as a reinforcing material, anion exchange capacity 1.5 meq / g, membrane resistance 2.4 Ω·cm²) was prepared.
[0215] As a catalyst particle coating solution, a suspension obtained by making an aqueous solution of tin chloride (II) at a concentration of 0.4 mass%, identical to that used in Example 1, was used.
[0216] The anion exchange membrane, having had irregularities formed on its surface beforehand with sandpaper (CC 200 Cw), was immersed in the catalyst coating solution at 25°C for 1 hour, and then air-dried at room temperature to distribute catalyst particles on its surface.
[0217] A solution for forming a cation exchange membrane was applied to one side of this anion exchange membrane, and a cation exchange membrane layer was formed by leaving it at room temperature to manufacture a bipolar membrane.
[0218] Here, as the solution for forming the cation exchange membrane, a solution of sulfonated polyetheretherketone dissolved in tetrahydrofuran at a concentration of 20 mass% was used.
[0219] The cation exchange capacity of the cation exchange membrane obtained by applying this solution for forming a cation exchange membrane onto a polyester film and leaving it at room temperature to dry was measured to be 2.1 meq / g. From this, it was confirmed that the cation exchange capacity of the cation exchange membrane layer in the above bipolar membrane is equivalent.
[0220] Regarding the above bipolar membrane, it was confirmed by the above method that the particles present at the interface between the cation exchange membrane and the anion exchange membrane are basic tin chloride (II) particles.
[0221] In addition, the amount of this basic tin chloride (II) was measured to be 0.4 g / m².
[0222] In addition, the basic tin chloride (II) particles had a number average particle size (Dn) of 2 μm and a hydroxide ion introduction degree T of 60%.
[0223] The results of measuring the characteristics of this bipolar membrane are shown in Table 1.
[0224] <Example 13>
[0225] A bipolar film was prepared by performing the same operation as in Example 1, except that the preparation of the catalyst particle coating solution in Example 1 was carried out by dissolving tin chloride (II) in water at a concentration of 0.01 mass% at 25°C.
[0226] Regarding the obtained bipolar membrane, it was confirmed by the above method that the particles present at the interface between the cation exchange membrane and the anion exchange membrane are basic tin chloride (II) particles.
[0227] In addition, the amount of this basic tin chloride (II) particle was measured to be 0.08 g / m².
[0228] In addition, the basic tin chloride (II) particles had a number average particle size (Dn) of 1 μm and a hydroxide ion introduction degree T of 82%.
[0229] The results of measuring the characteristics of this bipolar membrane are shown in Table 1.
[0230] <Example 14>
[0231] In Example 11, a bipolar membrane was prepared by performing the same operation as in Example 1, except that the amount of catalyst particle powder applied to the surface of the cation exchange membrane with a finger was adjusted, and the amount of basic ruthenium(III) chloride particles present at the interface between the cation exchange membrane and the anion exchange membrane in the obtained bipolar membrane was 6.0 g / m².
[0232] For the obtained bipolar membrane, the basic ruthenium chloride (III) particles had a number average particle size (Dn) of 3 μm and a hydroxide ion introduction degree T of 45%.
[0233] The results of measuring the characteristics of this bipolar membrane are shown in Table 1.
[0234] <Comparative Example 1>
[0235] In Example 1, a bipolar film was prepared by performing the same operation as in Example 1, except that a 2.5 mass% aqueous solution of tin(II) chloride was used as the catalyst particle coating solution.
[0236] For the obtained bipolar membrane, the amount of catalyst particles present at the interface between the cation exchange membrane and the anion exchange membrane was measured to be 0.4 g / m².
[0237] In addition, the number average particle size (Dn) of these catalyst particles was 6 μm, and the degree of hydroxide ion introduction T was 0%.
[0238] The results of measuring the characteristics of this bipolar membrane are shown in Table 1.
[0239] <Comparative Example 2>
[0240] In Example 4, a bipolar membrane was prepared by performing the same operation as in Example 4, except that the preparation of the catalyst particle coating solution was carried out by dissolving ruthenium(III) chloride in water at a concentration of 2.5 mass% at 25°C, adding sodium hydroxide to the solution under stirring to adjust the pH to 13.0, and leaving it for 30 minutes.
[0241] For the obtained bipolar membrane, the amount of catalyst particles present at the interface between the cation exchange membrane and the anion exchange membrane was measured to be 1.1 g / m².
[0242] In addition, the number average particle size (Dn) of these catalyst particles was 3 μm, and the degree of hydroxide ion introduction T was 100%.
[0243] The results of measuring the characteristics of this bipolar membrane are shown in Table 1.
[0244] In addition, the following abbreviations were used in Table 1.
[0245] Catalyst amount: Cat-am
[0246] Number average particle size (Dn): Nm-av(Dn)
[0247] Hydroxide ion introduction degree T: OHCPD-Int T
[0248] Flood Voltage: Wat-Volt
[0249] Flood Damage Efficiency: Wat-Eff
[0250] Delamination area: PL-Area
[0251] Flood voltage after long-term operation: LongDr Wat-Volt
[0252] Explanation of the symbols
[0253] BP: Bipolar membrane 1: Cation exchange membrane 3: Anion exchange membrane 5: Particles of basic metal chlorides
Claims
Claim 1 A bipolar membrane in which a cation exchange membrane and an anion exchange membrane are bonded, wherein particles of a basic metal chloride are distributed at the interface between the cation exchange membrane and the anion exchange membrane in an amount of 0.01 to 5 g / m², wherein the basic metal chloride has a composition expressed by the following formula (1). A bipolar membrane characterized in that, in the above formula, M is a polyvalent metal such as Sn or Ru, x and y are non-zero numbers whose sum is the valence of the polyvalent metal M, and the basic metal chloride has a hydroxide ion introduction degree T defined by the following formula (2) of 20 to 90%. Claim 2 A method for manufacturing a bipolar membrane comprising: a process of preparing a pre-fabricated ion exchange membrane as a substrate membrane; a particle distribution process of preparing a coating solution in which particles of a basic metal chloride are dispersed, applying and drying it on the surface of the substrate membrane to distribute the particles of the basic metal chloride on the surface of the substrate membrane in an amount of 0.01 to 5 g / m²; and a coating process of applying a counterion exchange resin solution to the surface of the substrate membrane in which the particles of the basic metal chloride are distributed, and drying it to form a counterion exchange resin layer on the substrate membrane, wherein the basic metal chloride has a composition expressed by the following formula (1). In the above formula, M is a polyvalent metal such as Sn or Ru, x and y are non-zero numbers whose sum is the valence of the polyvalent metal M, and the basic metal chloride is a method having a hydroxide ion introduction degree T of 20 to 90% as defined by the following formula (2). Claim 3 delete Claim 4 delete
Citation Information
Patent Citations
Bipolar membrane with amino polymer as middle catalytic layer and preparation method of bipolar membrane
CN106310950A
Bipolar membrane and its production
JP1992228591A
Bipolar membrane
KR100730009B1
High performance bipolar membranes
US5227040A
Method for making a bipolar membrane and use of resulting bipolar membrane
US6924318B2
